Dampak Dinamika Inflasi Dan Ukuran Perusahaan Terhadap Tingkat Penghindaran Pajak Pada 11 Sektor Industri Yang Listing Di Bursa Efek Indonesia (BEI) Pada Tahun (2019-2022) - prisilia, shofianti; R. Pandin, Maria Yovita (Universitas Dian Nuswantoro, 2024)
This study aims to determine the effect of inflation rate and company size on the level of tax avoidance. The population in this study are companies listed on the Indonesia Stock Exchange (IDX) in 2019-2022. The sampling technique was purposive sampling method. Data analysis using SEM-PLS with the help of SmartPLS4 analysis tool. Based on the results of the study, it can be concluded that the inflation rate has no effect on the level of tax avoidance, company size affects the level of tax avoidance. And the inflation rate and company size have no significant effect on the level of tax avoidance.